Comprehensive genomic and tumour immune profiling reveals potential therapeutic targets in malignant pleural mesothelioma - Jenette Creaney; Ann-Marie Patch; Venkateswar Addala; Sophie A. Sneddon; Katia Nones; Ian M. Dick; Y. C. Gary Lee; Felicity Newell; Ebony J. Rouse; Marjan M. Naeini; Olga Kondrashova; Vanessa Lakis; et al. (Genome Medicine, 2022)
Abstract Background Malignant pleural mesothelioma (MPM) has a poor overall survival with few treatment options. Whole genome sequencing (WGS) combined with the immune features of MPM offers the prospect of identifying changes that could inform future clinical trials. Methods We analysed somatic mutations from 229 MPM samples, including previously published data and 58 samples that had undergone WGS within this study. This was combined with RNA-seq analysis to characterize the tumour immune environment. Results The comprehensive genome analysis identified 12 driver genes, including new candidate genes. Whole genome doubling was a frequent event that correlated with shorter survival. Mutational signature analysis revealed SBS5/40 were dominant in 93% of samples, and defects in homologous recombination repair were infrequent in our cohort. The tumour immune environment contained high M2 macrophage infiltrate linked with MMP2, MMP14, TGFB1 and CCL2 expression, representing an immune suppressive environment. The expression of TGFB1 was associated with overall survival. A small subset of samples (less than 10%) had a higher proportion of CD8 T cells and a high cytolytic score, suggesting a ‘hot’ immune environment independent of the somatic mutations. Conclusions We propose accounting for genomic and immune microenvironment status may influence therapeutic planning in the future.